2022
DOI: 10.1039/d2tc02872g
|View full text |Cite
|
Sign up to set email alerts
|

Polarized SERS substrates with directionality, repeatability and orderability: an anisotropic Ag nanocavity array

Abstract: This paper reports the design and fabrication of an anisotropic Ag nanocavity array, which mainly uses magnetron sputtering and ion beam etching techniques to get the ordered Ag nanocavity array...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Compared to other photolithography methods, NSL can manufacture a large area of plasmonic sensing structures, which has lower production cost and is more practical [ 47 , 48 ]. In particular, the shape of nano-structures made by NSL is variable, which can be fabricated as three-dimensional nano-structures to a certain extent; thus, it increases the flexibility of structure design [ 49 , 50 ]. Yet, although NSL does not require photomask, which simplifies the manufacturing steps, there are possibly local defects in plasmonic arrays due to the fact that the colloidal spheres are not fully aligned in local areas in the self-assembly process, and it will affect the uniformity of the plasmon sensing structures.…”
Section: Fabrication Of Sensing Structure In Plasmonic Biosensorsmentioning
confidence: 99%
“…Compared to other photolithography methods, NSL can manufacture a large area of plasmonic sensing structures, which has lower production cost and is more practical [ 47 , 48 ]. In particular, the shape of nano-structures made by NSL is variable, which can be fabricated as three-dimensional nano-structures to a certain extent; thus, it increases the flexibility of structure design [ 49 , 50 ]. Yet, although NSL does not require photomask, which simplifies the manufacturing steps, there are possibly local defects in plasmonic arrays due to the fact that the colloidal spheres are not fully aligned in local areas in the self-assembly process, and it will affect the uniformity of the plasmon sensing structures.…”
Section: Fabrication Of Sensing Structure In Plasmonic Biosensorsmentioning
confidence: 99%
“…Therefore, more and more researchers focus on the design and construction of a nanocavity substrate. 24 The previous study reported that the nanoporous structures have an interconnected mesh structure and a large specific surface area, which can enhance the capacity to adsorb gas molecules. 27−29 However, the nanoporous structures are mainly prepared using oxidation 30 or dealloying techniques.…”
mentioning
confidence: 99%
“…Nanocavity structures mostly possess an array architecture with large “hot spot” areas and special optical focusing properties, which can increase the contact probability with the detector, thus improving the sensitivity and reproducibility of detection. Therefore, more and more researchers focus on the design and construction of a nanocavity substrate. The previous study reported that the nanoporous structures have an interconnected mesh structure and a large specific surface area, which can enhance the capacity to adsorb gas molecules. However, the nanoporous structures are mainly prepared using oxidation or dealloying techniques. The nanoporous structures prepared with the above methods are mostly random in distribution, which undermines the advantage of the SERS substrate in terms of reproducibility, and a result of the limitation of materials and preparation methods that hinder the formation of substrates with high flexibility and transparency, both of which hamper the application of such structures for in situ gas detection. , …”
mentioning
confidence: 99%